The Effects of Mindfulness-Based Stress Reduction on Negative Self-Representations in Social Anxiety Disorder—A Randomized Wait-List Controlled Trial - He, Liguo; Han, Wei; Shi, Zhan (Frontiers in Psychiatry, 2021)
This study examined the impact of Mindfulness-Based Stress Reduction (MBSR) versus Waitlist (WL) on the self-reference effect involving negative adjectives in individuals with social anxiety disorder (SAD). Eighty-five participants with SAD were randomly assigned to 12 weeks of MBSR or WL, and completed an incidental SRE task that assessed treatment-related negative self-representations. Self-related negative adjectives were worse remembered in MBSR than in WL, while other-related negative adjectives were better remembered in MBSR than in WL. No differences emerged between the levels of self- and other-related processing for adjectives in MBSR. Moreover, the MBSR-related decreases in the difference in recognition memory performance between self and other conditions, i.e., the treatment-related equilibrium, could predict the MBSR-related decreases in social anxiety symptoms. The selfless functioning and self-other control that can provide reasonable interpretations for these findings were discussed.